Black economic empowerment in a South African mining company. - Tsie, Thabang Moses (My University, 2017)
Prior to 1994, the majority of the South African population, in particular, Black people, were prevented from participating meaningfully in the mainstream economy by apartheid policies. These policies were aimed at guaranteeing that Black people were not allowed to participate in certain sectors of the economy and were not employed in senior management positions in both public and private sector entities. This state of affairs resulted in South Africa being racially divided into two nations, one nation comprised the minority of the population who owned industries and occupied senior management positions at places of work, the other nation, represented the majority of the population who were deprived of meaningful economic participation. To address this legacy of apartheid, the post 1994 democratic government introduced corrective policies that were aimed at transforming the South African economic landscape. The Black Economic Empowerment (BEE) policy was introduced to address the imbalances of the past and to bridge the gap that existed between these two nations. This paper explores key challenges and opportunities experienced in the course of implementing a BEE transaction at Northam Platinum Limited and whether or not economic benefits were transferred to Black people. Semi-structured qualitative interviews were used to collect data from ten senior managers who participated in the BEE transaction. A qualitative content analysis method was used to analyse collected data, and findings suggest that challenges experienced include the complexity of developing a sound business case for BEE transaction and the ability to communicate it to key stakeholders, the ability to convince equity owners to fund a BEE transaction, given the risks of ownership dilution and market performance, finding suitable broad-based groups of beneficiaries who share in the long-term strategic vision of the empowering company, and getting all stakeholders to agree on how benefits would be transferred to BEE beneficiaries. The study concludes that the BEE transaction was successful because significant economic benefits were directly transferred to Black people, in the form of equity and managerial positions were afforded to Black people. The broad-based nature of this BEE transaction, led to economic benefits being transferred to the majority of Black people where the empowering company has operations.
MBA Thesis
Keywords: Affirmative action programs,Blacks -- Employment -- South Africa,Mineral industries -- South AfricaEmployee empowerment -- South Africa